Proteomic analysis of kidneys from selenoprotein M transgenic rats in response to increased bioability of selenium - Goo, Jun Seo (Springer, 2013)
BACKGROUND: To characterize changes in global protein expression in kidneys of transgenic rats overexpressing human selenoprotein M (SelM) in response to increased bioabivility of selenium (Sel), total proteins extracted from kidneys of 10-week-old CMV/hSelM Tg and wild-type rats were separated by 2-dimensional gel electrophoresis and measured for changes in expression. RESULTS: Ten and three proteins showing high antioxidant enzymatic activity were up- and down-regulated, respectively, in SelM-overexpressing CMV/hSelM Tg rats compared to controls based on an arbitrary 2-fold difference. Up-regulated proteins included LAP3, BAIAP2L1, CRP2, CD73 antigen, PDGF D, KIAA143 homolog, PRPPS-AP2, ZFP313, HSP-60, and N-WASP, whereas down-regulated proteins included ALKDH3, rMCP-3, and STC-1. After Sel treatment, five of the up-regulated proteins were significantly increased in expression in wild-type rats, whereas there were no changes in CMV/hSelM Tg rats. Only two of the down-regulated proteins showed reduced expression in wild-type and Tg rats after Sel treatment. CONCLUSIONS: These results show the primary novel biological evidences that new functional protein groups and individual proteins in kidneys of Tg rats relate to Sel biology including the response to Sel treatment and SelM expression.